Circular renovation in construction at the meso scale: a systematic literature review and framework development - Ashrafi, Shahab; Vrijhoef, Ruben; Wamelink, Hans (Frontiers in Built Environment, 2025)
The construction sector is a significant contributor to global waste, highlighting the urgent need for circular practices. While the construction lifecycle includes phases such as construction, maintenance, renovation, and demolition, renovation is particularly complex—and integrating circularity adds further challenges. In circular renovation, material reuse and recovery are central goals. This study focuses on circular renovation within the construction sector, addressing a gap in current research through a systematic literature review of 121 publications. Based on the findings, a three-step process—Planning, Assessing, and Routing—is proposed, and associated methods, approaches, and tools are reviewed. Drawing on these insights, a new framework is developed from a meso-scale perspective, aimed at identifying material reuse cycles. Whereas most existing studies focus on individual projects (micro scale) or urban systems (macro scale), this research emphasizes the underexplored meso scale, promoting reuse across multiple projects through collaborative networks. This approach supports more sustainable construction practices and advances the broader objectives of the circular economy.